Cross-national changes in time-use: some sociological (hi)stories re-examined - Oriel Sullivan; Jonathan Gershuny (University of Essex, Institute for Social and Economic Research (ISER), 2001)
The paper addresses some macro-sociological questions about changes in broad categories of time-use. The focus is on large-scale cross-national time trends from developed countries in paid and unpaid work, and leisure. Reference is made to some well-known sociological and historical accounts of such change, and to the fact that time-use diary data has only relatively recently become available for analysing trends over time. The data used are drawn from a comparative cross-time data archive held by the Institute for Social and Economic Research at Essex University, comprising successive time-use diary surveys from a range of industrialized countries collected from the 1960s to the 1990s. The time use evidence suggests relative stability in the balance between work and leisure time over the period covered by the analyses. Some alternative explanations are advanced for why there seems to be a gap between this evidence and, on the other hand, the burgeoning literature in both academic and popular media addressing the time famine and, on the other, peoples professed experience of what is happening to their time.
Keywords: 330